ANALSIS DAMPAK KEBERADAAN PASAR CUNGKING TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PASAR CUNGKING KABUPATEN BANYUWANGI - Prima, Sugeng; Harjianto, Harjianto; Sabiq, Mohammad Sabiq Irwan Hariandi (JURNAL PENDIDIKAN IPS, 2025)
Traditional markets play a strategic role in supporting the economic and social activities of the community, one of which is Cungking Market, located in Banyuwangi Regency. This study aims to analyze the impact of Cungking Market on the social and economic life of the surrounding community. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects included traders, market managers, and the surrounding community. The results show that socially, Cungking Market has made a significant contribution in forming a strong social network, increasing interaction and tolerance between residents, and becoming a public space that facilitates harmonious social relations. Meanwhile, from an economic aspect, this market plays a role in increasing community income, opening business opportunities, and encouraging local economic growth. Cleanliness, orderliness, and active participation of residents in managing the market also make Cungking Market an example of a traditional market that is developing positively.